Danger zone: Men, masculinity and occupational health and safety in high risk occupations. (December 2015) - Stergiou-Kita, Mary; Mansfield, Elizabeth; Bezo, Randy; Colantonio, Angela; Garritano, Enzo; Lafrance, Marc; Lewko, John; Mantis, Steve; Moody, Joel; Power, Nicole; Theberge, Nancy; Westwood, Eleanor; et al.
Highlights: Men are more likely to die from work-related injuries than women. Little is understood about how masculinity can influence men's occupational health and safety (OH&S). In this review we explore masculinity and men's OH&S in high risk male-dominated occupations. Dominant masculine norms can affect perceptions, acceptance and normalization of risks in workplace contexts. Masculinity can intersect with other variables (e.g. age, labour market forces) to influence OH&S. Abstract: The workplace is a key setting where gender issues and organizational structures may influence occupational health and safety practices. The enactment of dominant norms of masculinity in high risk occupations can be particularly problematic, as it exposes men to significant risks for injuries and fatalities. To encourage multi-disciplinary collaborations and advance knowledge in the intersecting areas of gender studies, men's health, work and workplace health and safety, a national network of thirteen researchers and health and safety stakeholders completed a critical literature review examining the intersection between masculinities and men's workplace health and safety in order to: (i) account for research previously undertaken in this area; (ii) identify themes that may inform our understanding of masculinity and workplace health and safety and; (iii) identify research and practice gaps in relation to men's workplace health and safety. In this paper we present key themes from this review. Recommendations are made regarding: (i) how to define gender; (ii) how to attend to and identify how masculinities may influence workers' identities, perceptions of occupational risks and how institutionalized practices can reinforce norms of masculinity; (iii) the importance of considering how masculinities may intersect with other variables (e.g. historical context, age, class, race, geographical location) and; (iv) the added significance of present-day labour market forces on men's occupational health and safety.